(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides information on the great scientific significance of the study of the history of culture, scientific and technological progress of the peoples of Central Asia by Tashmukhammed Niyazovich Kara-Niyazi, as well as on the scientific research of the scientist